2019
DOI: 10.1021/acsbiomaterials.9b00064
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Extracellular Matrix-Modified Decellularized Tendon Slices Facilitate the Migration of Bone Marrow Mesenchymal Stem Cells

Abstract: It is highly desirable to develop a novel scaffold that can induce stem cell migration in tendon tissue engineering and regeneration. The objective of this study is to assess the effect of stem cell extracellular matrix-modified decellularized tendon slices (ECM-DTSs) on bone marrow mesenchymal stem cells (BMSCs) migration and explore the possible molecular mechanisms. Native ECM produced by BMSCs and tendon-derived stem cells (TDSCs) was deposited on DTSs, denoted as bECM-DTSs and tECM-DTSs, respectively, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…11,12,53 Our previous study also demonstrated that TDSCs could secrete chemokines similar to BMSCs, including SDF-1 and monocyte chemotactic protein 1, and decellularized tendon slices coated with TDSC-derived ECM notably improved BMSC migration compared with decellularized tendon slices. 66 In our study, the results of immunofluorescence staining showed that the hDCB-ECM group could recruit more endogenous stromal cells than the other 3 groups. However, there was no difference in stromal cell recruitment between the hDCB group and the DCB group.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…11,12,53 Our previous study also demonstrated that TDSCs could secrete chemokines similar to BMSCs, including SDF-1 and monocyte chemotactic protein 1, and decellularized tendon slices coated with TDSC-derived ECM notably improved BMSC migration compared with decellularized tendon slices. 66 In our study, the results of immunofluorescence staining showed that the hDCB-ECM group could recruit more endogenous stromal cells than the other 3 groups. However, there was no difference in stromal cell recruitment between the hDCB group and the DCB group.…”
Section: Discussionsupporting
confidence: 47%
“…In general, our results and previous studies demonstrated that SDF-1 from ECM could recruit endogenous stromal cells, and biglycan from ECM could further induce multidirectional differentiation of recruited stromal cells to promote healing of the tendon-bone interface. 66,68 Although the hDCB group had more new formation of bone and fibrocartilage than the DCB group, there was no significant difference in the results of micro-CT and biomechanical testing between the 2 groups. However, hDCB-ECM significantly improved the ultimate tensile stress and Young modulus of the tendon-bone interface compared with DCB.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The short stimulation time in cell proliferation may be due to the explosive release of biochemical factors from cell-derived ECM (Katagiri et al, 1990;Fujii et al, 2010). Our recent study also demonstrated that the chemokines (SDF-1) in ECM-modified tendon slices showed an initial burst release within 12 h (Yao et al, 2019). A previous study showed that BMSCs seeded on the demineralized region deposited thicker and more aligned collagen than those on the mineralized region (Zhou et al, 2020).…”
Section: Discussionmentioning
confidence: 74%
“…The mixed hydrogel with 75% cECM promoted the cardiac differentiation of human embryonic stem cells with increased expression of troponin T and Cx43, improved striation patterns of cardiac troponin I, and promoted contractile function of cardiac cells. It should be mentioned that most in vitro stem cell and CM studies involved cECM hydrogels were performed by seeding cells on the hydrogel surface 40‐43 . There may exist significant differences of topography and ECM component presentation between surface and inside of hydrogel.…”
Section: Discussionmentioning
confidence: 99%